Comparative analysis of aroma components and quality of Geotrichum candidum after space mutation breeding - Chen, Junjie; Li, Qianying; Wang, Jie; Chen, Weizhe; Zheng, Qikai; Zhong, Qingping; Fang, Xiang; Liao, Zhenlin (Frontiers in Microbiology, 2022)
The aroma-producing strain of Geotrichum candidum GDMCC60675 was taken as the research object, the composition of aroma-producing substances of G. candidum was studied, and the target strains of G. candidum suitable for food additives were screened out by mutagenesis. Methods: Mutants were obtained by space breeding. The colony morphology and cell morphology of the mutant strain were identified, the phylogenetic tree of the two strains was constructed, and the whole genome sequences of the wild strain and the mutant strain were compared. The aroma components and key odor compounds of the two strains were analyzed and compared by HS-SPME-GC-MS and E-nose detection, and the data were treated by ROAV analysis method. Results: a mutant strain of G. candidum was found with different characteristics of aroma production compared with wild-type G. candidum. It was found that its colony morphology and cell morphology were similar. However, it was found that the aroma-producing substances produced by the two strains were different, and the key difference compound was phenyl ethyl alcohol, which also proved that the two strains were different, and the main aroma note was different.